Development of a Decubitus Risk Assessment Instrument using Website Media on The Incidence of Decubitus - Supriyanti, Deni; Haryanto, Joni; Sulistyaningsih, Dwi Retno; Pairoh, Hasanah (Poltekkes Kemenkes Tanjung Karang, 2024)
Decreased quality of service in the ICU occurs due to decubitus conditions, namely localized tissue damage due to pressure on soft tissue over bony prominence and pressure from outside for an extended period, so the importance of instruments with the Braden scale is used as an effort to prevent decubitus. This study aims to develop a decubitus risk assessment instrument based on Virginia Henderson's theory on a website that can be applied in the ICU to prevent decubitus. This research is descriptive research using the Delphi approach method, which consists of two stages: a literature study, FGD, expert consultation, content validity tests, readability tests, and website-based applications. In the second stage, researchers will conduct instrument experiments on ICU nurses at RSI Sultan Agung Semarang, with a sample of 50 ICU nurses. The results showed that the instrument has strong validity, so the manufacture of instruments can continue at the stage of making website applications. The results of the validity and reliability test of the instrument obtained 11 instruments that were declared feasible to use with valid and reliable values of 0.714>0.70. ICU nurses can use the Virginia Henderson theory-based decubitus instrument with a website to prevent decubitus.